Estimation Uncertainty and Optimal Advertising Decisions - Aykac, A.; Corstjens, M.; Gautschi, D.; Horowitz, I. (Management Science, 1989)
In this paper we develop a normative model that is built on an empirically relevant foundation. We observe that decision makers, among them advertisers, rely on estimated relationships in reaching resource allocation decisions, and we investigate the normative implications of this process. In particular, we explore the effects of uncertainty stemming from the use of sample estimates of population parameters. In general, we find that ignoring this estimation-related uncertainty leads to suboptimal decisions.